Single institution, randomized study to compare the efficacy and safety between laparoendoscopic single-site (LESS) surgery and conventional laparoscopic surgery for Uretero-Pelvic Junction (UPJ) stone - Ab Rashid, Islah Munjih; Sung, Yong Cho; Yong, Hyun Park; Son, Hwancheol; Hyeon, Hoe Kim; Seung, Bae Lee; Hyeon, Jeong (2013)
Introduction and Objectives LESS has slowly adopted its role in current urological practice. The objective of our study is to confirm the efficacy and safety of laparoendoscopic single-site surgery (LESS) compared to conventional laparoscopic surgery for upper urinary tract stones